Uncovering university students’ communication patterns and limiting factors in an Indonesian online learning context using WhatsApp - Fatimatuz Zahro (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2022)
WhatsApp group is one of the most widely used online learning media. Communication patterns in the online teaching and learning processes are influenced by this media. This platform affects communication patterns in the online learning process. However, some students felt they did not enjoy teaching and learning using WhatsApp group. This qualitative study explored WhatsApp group as a communication pattern in teaching and learning process in a university, using observation and semi-structured interviews analyzed by using the concept from Tubbs, to gather data from five higher education students and a lecturer. Study findings expose that WhatsApp groups gave freely for higher education students to communicate. However, the social media showed weaknesses during the teaching and learning process, including poor internet connection and low phone memory capacity. The students seemed to be not disciplined. They could not regulate their time to learn. They could cheat the answer of their peers. In this regard, the lecturer had to be creative to encourage students’ participation. Therefore, the lecturer had some strategies to overcome it. The lecturer should be able to provide feedback to all students, create a fun class, and control students to be involved in class.